Hampered AMPK-ULK1 cascade in Alzheimer’s disease (AD) instigates mitochondria dysfunctions and AD-related alterations which are alleviated by metformin - Arnaud Mary; Samantha Barale; Fanny Eysert; Audrey Valverde; Sandra Lacas-Gervais; Charlotte Bauer; Sabiha Eddarkaoui; Luc Buée; Valérie Buée-Scherrer; Frédéric Checler; Mounia Chami (Alzheimer’s Research & Therapy)
Abstract The adenosine monophosphate-activated protein kinase (AMPK) and its downstream effector Unc-51 like autophagy activating kinase 1 (ULK1) represent a key cellular signaling node, the alteration of which likely contribute to AD development. This study investigated the AMPK-ULK1 pathway activation state in AD and the impact of its modulation on mitochondria structure and function as well as on AD-related alterations. We show in human sporadic AD and 3xTgAD mice brains a defective activating phosphorylation of ULK1 despite the active phosphorylation of AMPK. In addition, we reported defective p-AMPK and p-ULK1 in cells expressing the amyloid precursor protein with the familial Swedish mutation. We then show that the antidiabetic metformin (Met) drug-mediated AMPK-ULK1 cascade activation alleviates structural and functional mitochondrial abnormalities in AD cells and mice brains. Furthermore, in the 3xTgAD brains, it reduces the early accumulation of APP C-terminal fragments (APP-CTFs) as well as amyloid beta (Aβ) burden, microgliosis and astrogliosis occurring at a later disease stage. AMPK-ULK1 activation increases the localization of APP-CTFs within cathepsin D-positive lysosomal compartments and the recruitment of Iba1+ cells to Aβ plaques in vivo and enhances cathepsin D activity and phagocytic activity of microglia in vitro. Additionally, AMPK-ULK1 activation normalizes dendritic spine morphology in organotypic hippocampal slice cultures modeling AD and alleviates learning deficit in symptomatic 3xTgAD mice. Our study demonstrates potential therapeutic benefits of targeting AMPK-ULK1 cascade to reverse both early and late AD-related alterations, deserving further investigation in fundamental research and in human clinical studies.